Drivers and Dynamics of Forest and Grassland Ecosystems in the Altai Mountains: A Framework for National Park Conservation - Menghan Deng; Faxiang Hu; Wanli Ma; Wenchao Yang; Xiaofeng Luan (Land)
The Altai Mountains region, characterized by its unique biodiversity and significant ecological value, is increasingly under pressure from anthropogenic activities and climate change. This study investigates the spatial and temporal dynamics of forest and grassland ecosystems in the Altai Mountains National Park Candidate Area from 2000 to 2020, and proposes a comprehensive framework for the conservation and management of national parks. Through a detailed analysis of land cover changes, we observed significant forest expansion of 13.65% and grassland degradation of 11.69%. Rapid forest expansion occurred before 2010, followed by accelerated grassland degradation after that, with 2010 identified as the critical turning point. Our analysis highlights the role of key drivers, such as soil type, elevation, cropland expansion, and human activities, in shaping these ecosystems. Using Geodetector and propensity score matching methods, we evaluated the effectiveness of existing protected areas in mitigating forest and grassland loss. While protected areas effectively contributed to forest restoration, they were less successful in preventing grassland decline, underscoring the need for integrated management approaches. The findings from this study provide critical insights into ecosystem dynamics and conservation effectiveness, offering valuable guidance for the establishment of national-park-type protected areas and broader regional conservation efforts.